(untitled) (Linguostylistic Studies, 2023)
In linguistics, lexical semantics is one of the fundamental fields of study. The article highlights the issue of folkloristics in the context of lexical semantics, which is always relevant for studies. Studying the language of folklore is essential for understanding the traditional culture of the people and preserving the values of the nation embedded in rites, beliefs, and mythological images. Linguistic studies of the motivational productivity of lexical groups or semantic fields are closely related to texts (folklore, folk poetry, spell texts). Lexical units of “plants” microsystem in folklore texts from western Polissia are of great linguistic importance in this context. The internal form of many plants’ names can be traced quite clearly, as we can see when elucidating the motivation of such phytonomens as maivka, molodylnyk, nekhvoroshch, vinychchia, serporiznyk, durmanyk, zaiacha kapusta (rabbit cabbage). Unfortunately, we cannot always establish the motivation for a particular name of a plant, some of them are influenced by folk etymology, as in the case of aiir (derived from the Turkish name ağir). The study of motivational characteristics of botanical vocabulary is combined with the field of extra-linguistic semantics (mythological images, magical actions, ritual practices, symbolic images), which brings motivational models into the field of culture. Phytonyms often appear in folklore texts and manifest a special symbolic meaning in their structure, such as widow’s grass, hare’s ears, Tatar potion, sabers, and vydiuk. In many cases, the folk-creative basis of the motivation of plant names is found outside the folklore text, since we can only guess about the existence of such a text (for instance, the origin of the names of such plants as bozhe derevo (the God’s tree), artemizida, etc.). Depending on the functional role, the same phytonym can have different meanings, e.g. krovavnyk is equally applicable to yarrow and St. John’s wort. And medicinal marigolds, yellow pitcher plants, iron sedum, Asian honeysuckle, marsh marigolds, erect foxgloves, and celandine have the popular common name zhovtets (buttercup). The cultural, historical, and ethnographic features of the Ukrainians, their traditions, and worldview have a significant influence on the semantic features of lexical folklorisms.